Algoritmo para o problema de atribuição de papéis em redes de sensores sem fio - Fernanda Sumika Hojo de Souza (2007)
Recent technological advances allowed the combination of embedded systems and wireless communication, making possible a new type of mobile ad-hoc network, known as Wireless Sensor Network (WSN). These networks have the capacity to monitor the physical world through small sensors that operate in integrated and collaborative way. Due to the compact nature of the sensor nodes, one of the main focus in WSN's design is the energy constraint. In this way, studies aiming to improve the operation conditions of these networks, as well as extend its lifetime are very important. In this work the role assignment problem in WSN was studied, in which the objective is to define specific roles for the sensors, such that the network lifetime is maximized, guaranteeing the coverage of the demand points and the information routing. The problem was treated in different approaches, and the presented computational results show that it is possible to provide an improvement in the network design through optimization techniques.